2014
DOI: 10.1021/jp510641a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Neighboring Charged Group on Hydrophobic Hydration Shell Structure

Abstract: Raman multivariate curve resolution (Raman-MCR), as well as quantum and classical calculations, are used to probe water structural changes in the hydration shells of carboxylic acids and tetraalkyl ammonium ions with various aliphatic chain lengths. The results reveal that water molecules in the hydration shell around the hydrophobic chains undergo a temperature and chain length dependent structural transformation resembling that previously observed in aqueous solutions of n-alcohols. Deprotonation of the carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 33 publications
7
37
0
Order By: Relevance
“…The broad OH features at ∼3400 cm −1 is due largely to water molecules that are H-bonded to the carboxylate headgroup of C 9 COONa, as evidenced by the appearance of a very similar band in the hydration shell spectrum of sodium formate (HCOONa). 20 In order to suppress the SC OH band arising from the carboxylate headgroup hydration shell, and thus highlight features arising from the hydrophobic hydration shell of the surfactant's tail (C 9 ), we have implemented a Raman-MCR headgroup subtraction procedure by including an equimolar concentration of HCOONa in the solvent reference solution, as previously described. 20 In other words, since the carboxylate headgroup is now present in both the surfactant solution and in the solvent reference solution, the resulting Raman-MCR SC spectrum contains OH features arising primarily from the surfactant's hydrophobic hydration shell.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The broad OH features at ∼3400 cm −1 is due largely to water molecules that are H-bonded to the carboxylate headgroup of C 9 COONa, as evidenced by the appearance of a very similar band in the hydration shell spectrum of sodium formate (HCOONa). 20 In order to suppress the SC OH band arising from the carboxylate headgroup hydration shell, and thus highlight features arising from the hydrophobic hydration shell of the surfactant's tail (C 9 ), we have implemented a Raman-MCR headgroup subtraction procedure by including an equimolar concentration of HCOONa in the solvent reference solution, as previously described. 20 In other words, since the carboxylate headgroup is now present in both the surfactant solution and in the solvent reference solution, the resulting Raman-MCR SC spectrum contains OH features arising primarily from the surfactant's hydrophobic hydration shell.…”
Section: ■ Resultsmentioning
confidence: 99%
“…20 In order to suppress the SC OH band arising from the carboxylate headgroup hydration shell, and thus highlight features arising from the hydrophobic hydration shell of the surfactant's tail (C 9 ), we have implemented a Raman-MCR headgroup subtraction procedure by including an equimolar concentration of HCOONa in the solvent reference solution, as previously described. 20 In other words, since the carboxylate headgroup is now present in both the surfactant solution and in the solvent reference solution, the resulting Raman-MCR SC spectrum contains OH features arising primarily from the surfactant's hydrophobic hydration shell. Figure 2B shows headgroup-subtracted SC spectra obtained in this way, both below (0.05 M, blue) and above (1.0 M, red) the CMC of C 9 COONa (∼0.098 M).…”
Section: ■ Resultsmentioning
confidence: 99%
“…(55) These results showed that at low temperatures the hydration shells of each class has an enhanced water structure with greater tetrahedral order than the bulk, but for alcohols longer than 10 Å this structure disappeared as temperature increased. Additionally, at high pH onset of the hydration-shell structural transformation was suppressed by the carboxylate.…”
Section: Positive Curvaturementioning
confidence: 88%
“…The latter influences the pattern of HB network and acts as suppressor of dangling defects. 173 Finally, the waters near addends (ester-and phenyl group of PCBM and charged groups of FP family) build the HB network, which is characterized by a combination of four-and five membered cycles, i.e., network reveals greater tetrahedral ordering.…”
Section: E Dangling-oh Bonds and Hydrogen Bonds Pattern Near A Solutmentioning
confidence: 99%